THE SYSTEM OF VALUES AND THE ROLE OF ART IN MORAL AND AESTHETIC EDUCATION: METHODOLOGICAL APPROACHES IN THE TRAINING OF FUTURE TEACHERS (Web of Teachers: Inderscience Research, 2025)
This article analyzes the philosophical, pedagogical, and aesthetic dimensions of values, highlighting their role in personal development and the educational process. The study scientifically examines the influence of art, particularly visual arts, on the formation of values. The research demonstrates the aesthetic and educational potential of art, emphasizing its importance in fostering students’ moral maturity, aesthetic sensibility, and creative thinking. A comprehensive understanding of the system of values strengthens the professional training of future teachers and substantiates the effectiveness of implementing approaches in education that are based on moral and cultural values.